Some Unsettled Questions in Organization Theory - Millman, R. William (Academy of Management Journal, 1964)
This article attempts to call attention to the real issue in organization theory and to suggest the desirability for ending the time-consuming and wasteful debates of the past. The real issue is the need to recognize that different levels of general theory exist; that developments at all levels are needed; that research should be directed toward developing explanations of phenomena. In the process the individual researcher must select from among many possibilities: the approach to analysis, the type of analysis, the framework of analysis, and the unit of analysis best suited to his particular research question.